A comprehensive case study of climate change impacts on the cooling load in an air-conditioned office building in Malaysia - Yau, Y.H.; Hasbi, S. (2017)
In an earlier paper [1], the authors had comprehensively reviewed the climate change impacts for commercial buildings and their technical services in the tropics, and it revealed that numerous studies have been conducted to assess the climate change impacts in terms of energy consumption of a building. However, only few studies were carried out in the tropical region. This study aims to project the future cooling load needed for the years of 2000, 2020, 2050 and 2080 in the tropics using the TRNSYS simulation. Based on the simulation results, the total cooling load increases as the temperature changes. The total maximum cooling loads required in the years of 2000, 2020, 2050 and 2080 are 297000 kJ/hr, 305000 kJ/hr, and 332000 kJ/hr, respectively. When compared of the year 2000, the maximum cooling load needed in the years of 2020, 2050 and 2080 increases by 2.96%, 8.08% and 11.7% respectively. Based on the simulation results, in the next 70 years, the efficiency and durability of the existing system is predicted to decrease.